Clinical Application and Outcomes of Over the Scope Clip Device: Initial US Experience in Humans. (14th July 2013) - Jayaraman, Vijay; Hammerle, Christoper; Lo, Simon K.; Jamil, Laith; Gupta, Kapil
Abstract : Background . OTSCs are now available in the US for various indications. Methods . Retrospective review of OTSCs used from January 2011 to April 2012. Results . Twenty-four patients underwent placement of 28 OTSCs. Indications included postsurgical fistula, perforations, anastomotic leak, prophylactic closure after EMR, postpolypectomy bleeding, tracheoesophageal fistula, and jejunostomy site leak. Instruments used to grasp the tissue were dedicated (bidirectional forceps or tripronged device) and nondedicated devices (rat/alligator forceps or suction). Success was higher with nondedicated devices (12.5% versus 86.5%, P = 0.0004 ). Overall, OTSC was effective in 15/27 procedures. Defect closure was complete in 12/21. Mean followup was 2.9 months (1–8 m). Mean defect size was 10 mm (5–25 mm). A trend towards higher success was noted in defects <10 mm compared to defects >10 mm (90% versus 60%; P = 0.36 ). No difference was noted in closure of fresh (<72 hrs) versus chronic defects (>1 month) (75% versus 67%). There were no complications. Conclusion . The OTSC provides a safe alternative to manage fistula, perforation, and bleeding. No significant difference was seen for closure of early fistula or perforations as compared to chronic fistula. Rat-tooth forceps or suction was superior to the dedicated devices.